Comparison of CWT with DWT for detecting Qrs Complex on Wearable ECG Recorder - Uk-Jin Yoon; In-Seop Hwang; Yeon-Sik Noh; In-Cheol Chung; Hyung-Ro Yoon (2010 International Conference on Wavelet Analysis and Pattern Recognition, 2010)
Wearable ECG Recorder can detect not only Biosignal but also Motion artifact and other surrounding noises. This study used wavelet transform as a way of removing such noise and compared Continuous Wavelet Transform (CWT) and Discrete Wavelet Transform (DWT). Each transform is designed to optimize the QRS Complex. CWT was designed to detect the Maximum energy scale from QRS Complex. DWT was designed to decompose 8-Levels and to reconstruct detailed coefficient with the frequency of the QRS Complex. To test the performance of two methods, data were collected from MIT-BIH Arrhythmia Database and Wearable ECG Recorder(WER) at the speed of 3km/h, 6km/h, 9km/h, 12km/h. By analyzing the data from two methods, the effectiveness for detecting QRS Complex while eliminating the surrounding noises.